Morphological, anatomical, genetical and high performance thin layer chromatography profiling of Buddleia indica (Scrophulariaceae) - Youssef, Fadia S.; Ashour, Mohamed L.; Wink, Michael (Flora, 2018)
Buddleia indica Lam is an evergreen African shrub, native to Madagascar. Botanical investigations were done on the entire fresh plant leaves, old and young roots and stems, their histological sections as well as air-dried finely powdered samples. Genetic profiling and DNA fingerprinting were accomplished using RAPD-PCR technique (Random Amplified Polymorphic DNR- Poymerase Chain Reaction). Preliminary metabolic screening was performed using high performance thin layer chromatography (HPTLC) analysis. Botanical study of Buddleia indica revealed the presence of non -glandular 4-armed stellate trichomes, cruciferous stomata in the leaves, and the existence of U- shaped median vascular strand accompanied by small accessory bundles in the wings of its petiole all showed its close similarity to the Buddleioideae. Additionally, the cork in the stem that arouses from the pericycle (pericylic cork) and the pericycle which forms a loose ring of fibers surrounding the collateral vascular bundles are common characteristic among the members of Buddleioideae On the genetic level, it can be concluded that the most discriminative and relevant fragment resulting from the successful combination of template and primer was that produced by two primers OPA-09 and OPA-06 followed by OPA-07 RAPD primers attributing to the generation of 14, 13 and 12 amplified DNA fragments. Examination of HPTLC chromatograms of the leaves methanol extract showed ten major spots existing at different percentages that give bluish green color upon spraying with ferric chloride solution indicating its richness by phenolic compounds. Buddleia indica is rich in phenolic compounds and it belongs to Buddleioideae owing to the botanical resemblance.